A new schistosome (Digenea: Schistosomatidae) from the nasal tissue of South America black-necked swans, Cygnus melancoryphus (Anatidae) and the endemic pulmonate snail Chilina gibbosa - Flores, Verónica; Viozzi, Gustavo; Casalins, Laura; Loker, Eric Samuel; Brant, Sara Vanessa (Zootaxa, 2021)
To date, 9 species of Schistosomatidae have been found parasitizing the nasal tissues of mammal and bird hosts in the Eastern Hemisphere, 5 species in Rwanda (Africa), 2 in Australia (Oceania) and 2 in Eurasia. During a parasitological survey of black necked swans, Cygnus melancoryphus, an anatid endemic to South America, schistosome worms in the nasal tissue were found; the first in the Americas. Morphological results based on male worms and in isolated eggs. The worms have a spiny tegument, filiform body with rounded posterior end, two muscular suckers, a robust gynaecophoric channel with thickened cross bands, and around 130 testes. The eggs are elongate with an asymmetrical bulge, with a slender process at one end and a longer curved process at the other. Diagnostic morphological characteristics do not match with any schistosome genus. Part of the mitochondrial cox1 and nuclear DNA 28S partial genes were sequenced and compared to Schistosomatidae in GenBank. The genetic results confirm the distinctiveness of the specimens since they do not group with any described genus or undescribed lineage other than cercariae of “Chilina lineage 1” that emerge from the Patagonian Chilina gibbosa, a freshwater snail endemic to South America. Based on morphological and genetic characterization of these schistosomes, these specimens represent a new genus and species that parasitizes black necked swans as adults in the nasal tissue, and C. gibbosa is the first intermediate host, both hosts being endemic to South America.